Upaya Penanganan Khusus Narapidana Lansia sebagai Kelompok Rentan - Sifra Lidya, Elika; Subroto, Mitro (Jurnal Syntax Fusion, 2021)
LAPAS or Correctional Institution under the auspices of the Directorate General of Corrections is the final place of the criminal justice system process that fosters and integrates the social of convicts, so that when returning to society they are able to live a normal life. Elderly (according to Law No. 13 of 1998: Elderly) is a person whose age reaches the age of 60 years and above. In its efforts, Correctional Services interpret this understanding by regulating the rights of inmates contained in Law no. 12 of 1995 article 14 paragraph 1.The increasing age and declining body condition of the elderly inmates need special treatment both in health, treatment, and public services. Elderly inmates as much as possible are treated as people usually are, it's just that the place and application are different. This is for the implementation of part of Human Rights (HAM) as a national instrument. This special handling effort involves other stakeholders be it medical or health workers and the government to support the infrastructure needed. The elderly as one of the vulnerable groups become important objects in terms of how decent handlers are so that they feel cared for in their twilight years. Although until now still in the process and stages of refinement of special handling for them. The fact is still not optimal and this study illustrates how well the effort is.